Characterization of the hepatic flora and metabolome in nonalcoholic fatty liver disease - Jiang, Hua; Wang, Hui; Guo, Yangfan; Zhu, Yankun; Dai, Hui; Liang, Chenchen; Gao, Jianpeng (Frontiers in Microbiology, 2024)
Background/aimThe purpose of this study was to examine the hepatic bacterial composition and metabolome characteristics of patients with NAFLD using 16S rDNA sequencing and metabolomics. The results of the study revealed substantial differences in hepatic bacterial composition and metabolites between the NAFLD group and the control group. These differences were used to identify potential biomarkers that could be employed to diagnose NAFLD.Subjects/methodsLiver tissues from 13 patients in the NAFLD group and 12 patients in the control group were collected for microbiota examination.ResultsThe bacterial DNA profiles of the liver were significantly different between NAFLD patients and controls. NAFLD patients exhibited an enrichment of Enterobacterales, Mycobacteriales, Pseudomonadales, Flavobacteriales and Xanthomonadales, Sphingomonadales, Lysobact, which was characterised by a lack of erales. At the genus level, the abundance values of Escherichia-Shigella, Rhodococcus, and Chryseobacterium in the NAFLD group were significantly elevated, while the abundance values of Stenotrophomonas, Lawsonella and Sphingobium were significantly reduced. A total of 402 distinct metabolites were identified between the two groups, with 78 metabolites that were up-regulated and 14 metabolites that were down-regulated. The enrichment of metabolic pathways indicated that linoleic acid metabolism was the most significant contributor to the metabolic differences, and lipid metabolism was substantially differentiated. The hepatic metabolite levels were substantially correlated with the changes in hepatic microflora, as demonstrated by the correlation analysis.ConclusionDifferences in pathogenesis and host physiological function of NAFLD may be attributed to the hepatic flora and metabolomic characteristics. In the future, this presents new opportunities for the investigation of prospective diagnostic and therapeutic targets for NAFLD.